2022
DOI: 10.3390/antiox11020233
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cells in Atherosclerosis

Abstract: Atherosclerosis is a chronic progressive disease that involves damage to the intima, inflammatory cell recruitment and the accumulation of lipids followed by calcification and plaque rupture. Inflammation is considered a key mediator of many events during the development and progression of the disease. Various types of inflammatory cells are reported to be involved in atherosclerosis. In the present paper, we discuss the involved inflammatory cells, their characteristic and functional significance in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 121 publications
0
30
0
Order By: Relevance
“…Monocytes and macrophages may change their characteristics, secondary to pro-atherogenic stimuli [ 95 ], and participate in plaque formation [ 96 ]. After endothelial damage, the chemoattractant protein-1 (MCP-1) derived from macrocytes will initiate monocyte migration and secondary foam cell formation, as monocytes are believed to represent one of the initial steps of atherogenesis [ 97 ]. The progression of plaques is also related to lymphocyte activation, including B2 and T lymphocytes [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes and macrophages may change their characteristics, secondary to pro-atherogenic stimuli [ 95 ], and participate in plaque formation [ 96 ]. After endothelial damage, the chemoattractant protein-1 (MCP-1) derived from macrocytes will initiate monocyte migration and secondary foam cell formation, as monocytes are believed to represent one of the initial steps of atherogenesis [ 97 ]. The progression of plaques is also related to lymphocyte activation, including B2 and T lymphocytes [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these findings, the present study demonstrated that the three BTMs were not significantly associated with CIMT in T2DM patients. Furthermore, clinical studies investigating the association of serum osteocalcin and CVD risk are controversial, and the lack of consistency may be due to different study populations or different degrees of confounding factors associated with serum osteocalcin level, such as metabolic factors and chronic low-grade inflammation, and these metabolic dysfunctions are related to the progression of atherosclerosis ( 34 36 ). In humans, bone turnover rate varies obviously according to individual variables, age and sex are the most important variables determining bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Classical DCs (cDCs) and plasma cells-like DCs (pDCs) have been detected in both mouse and human atherosclerotic lesions. 26 Several subtypes of cDCs have been detected in the artery tissues, including CD103 + DCs, CD11b + DCs and CCL17 + DCs. DCs act as central instigators of the immune response and exert both pro-atherogenic and anti-atherogenic effects.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Classical DCs (cDCs) and plasma cells‐like DCs (pDCs) have been detected in both mouse and human atherosclerotic lesions 26 . Several subtypes of cDCs have been detected in the artery tissues, including CD103 + DCs, CD11b + DCs and CCL17 + DCs.…”
Section: Immune Cells On the Progression Of Atherosclerotic Plaquementioning
confidence: 99%